Fostering the practice of rooming-in in newborn care - Saurabh R. Shrivastava; Prateek S. Shrivastava; Jegadeesh Ramasamy (Journal of Health Sciences, 2013)
Practice of rooming-in meant that baby and mother stayed together in the same room day and night in the hospital, right from the time of delivery till the time of discharge. Adoption of rooming-in offers multiple benefits to the newborn, mother, and mother-child as a unit. It is a cost-effective approach where fewer instruments are required and spares additional manpower. Rooming-in endeavors the opportunity to contribute signifi cantly in the child’s growth, development and survival by assisting in timely initiation of breastfeeding. To ensure universal application of rooming-in in hospitals, a comprehensive and technically sound strategy should be formulated and implemented with active participation of healthcare professionals. Measures such as advocating institutional delivery through outreach awareness activities; adoption of baby-friendly hospital initiative; inculcating a sense of ownership among health professionals, can be strategically enforced for better maternal and child health related outcomes.